Analisis Batugamping Sebagai Bahan Baku Semen Di Desa Gombang Kabupaten Gunung Kidul - Hardiyanto, Dwi Wahyu; Pandita, Hita (Universitas Diponegoro, 2025)
The Wonosari Formation is composed of reef limestone, which possesses excellent qualifications as raw material for cement production. However, the presence of the Gunung Sewu Geopark has limited the permissible mining areas, making it interesting to study its potential not only as cement raw material but also for other products. The quality and quantity levels of the limestone are of significant importance in both scientific and industrial contexts. The genesis of the limestone in the study area consists of muddy allochem limestone and muddy micrite. Porosity tests indicate that the limestone has a generally moderate to good porosity level, ranging from 15% to 20%, with dominant structures of vug and channel types. Chemically, it meets the standard requirements for economically viable cement raw material, with SiO₂, Al₂O₃, Fe₂O₃, MgO, and SO₃ contents below 5%, and CaO content above 50%.